PROCEDURAL APPROACH TO THE DEVELOPMENT OF MODELS OF EDUCATION QUALITY MANAGEMENT IN THE SPHERE OF PHYSICAL CULTURE AND SPORT IN POLAND - Mozolev, Oleksandr (Continuing Professional Education: Theory and Practice, 2019)
The article analyses the views of Polish scientists on procedural approaches in the management of the quality of education. The structure is considered and content of the procedural approach to the work of the State Accreditation Commission is covered. Author’s vision is formed on the concept of "quality of management of development of education in the sphere of physical culture and sport of Poland. It is established that the procedural approach to quality management education in the sphere of physical culture and sport in Poland is a combination and interaction of legal, regulatory, administrative influences on the subjects of management system in order to correct their activities, creating the necessary financial, organizational, logistical, personnel, scientific, didactic, information, medical, economic, social and other conditions to ensure that an adequate level of stability and quality of provided educational services. The principles of making procedural model of education quality management in the sphere of physical culture and sport of Poland. It is defined that the processes of standardization of quality management education in the sphere of physical culture and sports is a part of the unified quality management system. Management solutions and their quality are determined by the contents of the regulatory administrative acts and procedures for their implementation, perfection and the effectiveness of the mechanisms of planning, forecasting, monitoring, evaluation and control.